2021
DOI: 10.14414/jebav.v23i3.1668
|View full text |Cite
|
Sign up to set email alerts
|

Indonesian Export Analysis: Autoregressive Distributed Lag (ARDL) Model Approach

Abstract: There are some factors predicted tohave an effect on the countries’ economic devlopment. This study aimed to analyze the long-term and short-term effects of In-flation, Exchange Rate, and Foreign Economic Growth (the destination of the United States, China, and Japan) on the Indonesian Export. The Auto-Regressive Distributed Lag (ARDL) Model is used in this analysis from 1968 through 2017. The results of the analysis show that in the long-term, the inflation and the economic growth in China as well in Japan ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 11 publications
1
3
0
Order By: Relevance
“…They found that the efficacy of the forecast results was being outperformed by the Vector Autoregressive Model (VAR) with only one lag. The result of this study also agrees with Labibah, Jamal, & Dawood (2021), who established ARDL with 1 lag model as the best model. Forecasting future value depends on the last value of the variable in question since it contains the most information.…”
Section: Resultssupporting
confidence: 92%
“…They found that the efficacy of the forecast results was being outperformed by the Vector Autoregressive Model (VAR) with only one lag. The result of this study also agrees with Labibah, Jamal, & Dawood (2021), who established ARDL with 1 lag model as the best model. Forecasting future value depends on the last value of the variable in question since it contains the most information.…”
Section: Resultssupporting
confidence: 92%
“…Table 1 shows the results of the unit root test using Augmented Dickey-Fuller, which demonstrated that the variables under examination are stationary at the level and first difference. The presence of unit roots in the data suggests that shocks have a long or short term impact (Labibah et al, 2021). Figure 1 shows the trend in Nigerian coffee production from 1981 to 2019, as well as a 10-year prediction.…”
Section: Resultsmentioning
confidence: 99%
“…The ARDL is used on time series data with integration orders of I (0) and I (1) (i.e. mixed order of integration) to generate an unbiased long-run estimate where a long-run connection exists (Bawa et al, 2016;Udoh et al, 2015;Labibah et al, 2021). The fundamental justification for using an ARDL model must be provided by an underlying economic theory or model, such as the neoclassical growth model.…”
Section: The Auto-regressive Distributed Lag Modelmentioning
confidence: 99%
“…Nilai ECT pada Tabel 6, baik model hybrid maupun model makro, memiliki koefisien negatif dan signifikan. Hal tersebut mengartikan bahwa model tersebut dapat terkoreksi dan mencapai keseimbangan jangka panjangnya (Labibah et al, 2021). Dalam jangka pendek, variabel mikrostruktur memiliki pengaruh yang Kammoun, 2021).…”
Section: Pengaruh Model Hybrid Terhadap Nilai Tukar Menggunakan Ardlunclassified